Halal Korean cosmetics: Factors shaping female students’ consumption intention in private Islamic universities - Sudarsono, Heri; Ash Shidiqie, Jannahar Saddam; Sujono, Rusny Istiqomah; Suciningtias, Siti Aisiyah; Fitriyani, Yeni; Khasanah, Miftakhul; Ikawati, Retty; Hawariyuni, Weni (International Journal of Halal Industry, 2025)
Purpose – This study aimed to test and analyze the role of Country of Origin, Halal Literacy, Attitude, Subjective Norms, and Perceived Behavioral Control on Intention Behavior and User Behavior in the context of Korean halal cosmetics consumption among female students. Methodology – This study used a quantitative approach with partial least squares-based Structural Equation Modeling (SEM) method (PLS-SEM). Data were collected through an online questionnaire with a 5-point Likert Scale from 223 female respondents across seven private Islamic universities. Data analysis involved evaluating the measurement and structural models to test the validity, reliability, and significance of the hypotheses. Findings – Country of origin is the strongest predictor of attitude and positively affects both intention and user behavior. Intention strongly predicts user behavior, confirming that strong intentions lead to actions. Interestingly, halal literacy positively affects attitude, but negatively influences intention, indicating that deeper knowledge makes consumers more critical. Implications – Korean halal cosmetics manufacturers need to highlight their reputation for innovation and product quality. Marketing strategies should focus on building trust and a positive brand image to form strong behavioral intentions rather than relying solely on halal education. Originality – This study offers novelty by integrating country of origin and halal literacy variables into one extended model, as well as testing the intention and actual usage behavior of a homogeneous consumer segment, namely female students at Islamic universities.